Characterization of tubular liquid crystal structure in embryonic stem cell derived embryoid bodies. Issue 1 (December 2017) - Xu, MengMeng; Jones, Odell; Wang, Liyang; Zhou, Xin; Davis, Harry; Bryant, Joseph; Ma, Jianjie; Isaacs, Willian; Xu, Xuehong
Abstract Background Massive liquid crystal droplets have been found during embryonic development in more than twenty different tissues and organs, including the liver, brain and kidney. Liquid crystal deposits have also been identified in multiple human pathologies, including vascular disease, liver dysfunction, age-related macular degeneration, and other chronic illnesses. Despite the involvement of liquid crystals in such a large number of human processes, this phenomenon is poorly understood and there are no in vitro systems to further examine the function of liquid crystals in biology. Results We report the presence of tubular birefringent structures in embryoid bodies (EBs) differentiated in culture. These birefringent tubular structures initiate at the EB surface and penetrated the cortex at a variety of depths. Under crossed polarized light, these tubules are seen as a collection of birefringent Maltese crosses and tubules with birefringent walls and a non-birefringent lumen. The fluidity of these birefringent structures under pressure application led to elongation and widening, which was partially recoverable with pressure release. These birefringent structures also displayed heat triggered phase transition from liquid crystal to isotropic status that is partially recoverable with return to ambient temperature. These pressure and temperature triggered changes confirm the birefringent structures as liquid crystals. The first report of liquid crystal so early in development. Conclusion The structure of the liquid crystal tubule network we observed distributed throughout the differentiated embryoid bodies may function as a transportation network for nutrients and metabolic waste during EB growth, and act as a precursor to the vascular system. This observation not only reveals the involvement of liquid crystals earlier than previously known, but also provides a method for studying liquid crystals in vitro.